First Complex Systems Digital Campus World E-Conference 2015 - Parrend, Pierre ; Bourgine, Paul ; Collet, Pierre (Springer, 2020)
This book contains the proceedings as well as invited papers for the first annual conference of the UNESCO Unitwin Complex System Digital Campus (CSDC), which is an international initiative gathering 120 Universities on four continents, and structured in ten E-Departments. First Complex Systems Digital Campus World E-Conference 2015 features chapters from the latest research results on theoretical questions of complex systems and their experimental domains. The content contained bridges the gap between the individual and the collective within complex systems science and new integrative sciences on topics such as: genes to organisms to ecosystems, atoms to materials to products, and digital media to the Internet. The conference breaks new ground through a dedicated video-conferencing system - a concept at the heart of the international UNESCO UniTwin, embracing scientists from low-income and distant countries. This book promotes an integrated system of research, education, and training. It also aims at contributing to global development by taking into account its social, economic, and cultural dimensions. First Complex Systems Digital Campus World E-Conference 2015 will appeal to students and researchers working in the fields of complex systems, statistical physics, computational intelligence, and biological physics.From Individual to Social Cognition: Piaget, Jung, and Commons; 1 Introduction; 2 Designing Education as a Flow Process; 3 Education as a Common; 4 Design Thinking, Cuisine, and Education; 5 The Schools of the Future; 6 Final Considerations; 7 Scientific Validation; References; POEM-COPA Collaborative Open Peer Assessment; 1 Introduction; 2 Peer Evaluation of Open Answers to Open Questions; 3 Principles and Implementation of COPA; 3.1 COPA Phase 1; 4 COPA Phase 2; 4.1 Answering 3 Questions; 4.2 Constrained Evaluation of Questions.